Pulmonary embolism: 'the great masquerader' of pneumonia in a patient with progressive supranuclear palsy - Robin G Manappallil; Vinod Krishnan (SpringerOpen, 2016)
Patients with Parkinson's disease are at risk of developing aspiration pneumonia. Pulmonary embolism is a rare but life-threatening complication in such patients, but could the same be true in progressive supranuclear palsy, an atypical form of Parkinsonism? This case report aims at highlighting the development of unprovoked pulmonary embolism in a patient with progressive supranuclear palsy and also describes how pulmonary embolism can mimic pneumonia in such patients.